Analisis Media Monitoring Terhadap Popularitas Evos Esports pada Bulan Maret 2024 - Putri, Tiara Harjono; Priyatna, Centurion Chandratama (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The esports industry is rapidly growing in Indonesia. This can be seen from data provided by the Indonesia Esports Premier League (IESPL), which ranks Indonesia 12th in the global gaming market, with a total of 62.1 million active gamers. The increasing growth of the esports industry reflects the rising popularity of esports in Indonesia. One highly popular esports club is Evos Esports, which has proven its prominence through numerous international tournament victories. Evos' popularity is also evident from its large following on TikTok, YouTube, Instagram, and Facebook, totaling more than 6 million followers. This underscores the need for media monitoring aimed at brand insight monitoring. The research methodology used in this study is a case study approach with a descriptive qualitative approach. Data collection techniques utilize media monitoring analytical tools such as Brand24. Information is collected using segmentation based on time, with data gathered from platforms including Twitter, TikTok, videos, news, podcasts, forums, blogs, and websites. The results of this study indicate that the popularity of Evos Esports increased in March 2024 due to its participation in the Mobile Legends Professional League Indonesia Season 13 (MPL ID).